2020
DOI: 10.1186/s40945-020-00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between timed up and go, usual gait speed and dizziness handicap inventory in elderly with vestibular disorders: a retrospective and analytical study

Abstract: Background: This study was done to verify the associations between the usual gait speed (UGS), the Timed Up and Go test (TUG), and the perception of disability in elderly vestibular patients and to identify factors associated with TUG results. Methods: This was a descriptive, analytical, and retrospective study that used data from the clinical records of vestibular patients aged 65 years or older at a rehabilitation service in Buenos Aires, Argentina. The records were examined for the following information: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Mean DHI score was 5.6 ± 11.2, consistent with the absence of self-reported dizziness handicap in healthy people 70 years and older (11). In patients with vestibular disorders aged 65 years or higher, the DHI score has been shown to have a significant association with the Timed Up and Go test and usual gait speed using the timed 10-meter walk test (12). Older patients with dizziness score higher in DHI than younger patients (13)(14)(15) and also multimorbidity is correlated to higher DHI scores (16).…”
Section: Introductionsupporting
confidence: 66%
“…Mean DHI score was 5.6 ± 11.2, consistent with the absence of self-reported dizziness handicap in healthy people 70 years and older (11). In patients with vestibular disorders aged 65 years or higher, the DHI score has been shown to have a significant association with the Timed Up and Go test and usual gait speed using the timed 10-meter walk test (12). Older patients with dizziness score higher in DHI than younger patients (13)(14)(15) and also multimorbidity is correlated to higher DHI scores (16).…”
Section: Introductionsupporting
confidence: 66%
“…The Dizziness Handicap Inventory (DHI), a 25-item self-assessment scale designed to measure the self-perceived level of handicap associated with the symptom of dizziness, has been proposed to assist in the diagnosis of BPPV and quantify the handicapping effects of dizziness in vestibular disorders [5,6]. Previous studies have shown that there are significant differences in DHI scores between healthy people and BPPV [5,7]. However, DHI is based on self-perception of disease and therefor there is still a lack of an objective tool to assess the severity of BPPV disease associate with dizziness handicapping.…”
Section: Introductionmentioning
confidence: 99%
“…In the classic study of Podsiadlo and Richardson, the correlation of TUG and gait speed was r = −0.61 [23]. Pearson's correlation coefficient between the usual gait speed (UGS) and the TUG test was r = −0.66 (p < 0.001) in elderly vestibular patients [44]. Functional gait assessment (FGA) correlated with TUG (r= −0.84, p < 0.001)(Spearman correlation coefficient) in 35 community-dwelling older adults [45].…”
Section: Discussionmentioning
confidence: 94%